Skeleton man - Bruchac, Joseph, 1942-; Comport, Sally Wern (New York : HarperCollins Publishers, 2001)
After her parents disappear and she is turned over to the care of a strange "great-uncle," Molly must rely on her dreams about an old Mohawk story for her safety and maybe even for her life.
7 9 13 18 26 30
Keywords: Psychopaths -- Fiction; Kidnapping -- Fiction; Mohawk Indians -- Fiction; Indians of North America -- New York (State) -- Fiction